2005
DOI: 10.1111/j.1467-9566.2005.00477.x
|View full text |Cite
|
Sign up to set email alerts
|

Access, boundaries and their effects: legitimate participation in anaesthesia

Abstract: The distribution of work, knowledge and responsibilities in the delivery of anaesthesia has attained particular significance recently as attempts to meet the demands of the European Working Times Directive intensify existing pressures to reorganise anaesthetic services. Using Lave and Wenger's (1991) notions of 'legitimate peripheral participation' in 'communities of practice ' (and Wenger 1998) to analyse ethnographic data of anaesthetic practice we illustrate how work and knowledge are currently configured, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 17 publications
(33 reference statements)
0
39
0
Order By: Relevance
“…On the other, we have much less formal groupings of clinical practitioners, often interprofessional, sometimes temporary confi gurations, sometimes permanent, brought together in a combined effort to deliver health care to a particular patient. We have also suggested that within the latter groupings (CoCPs) professional boundaries may be less distinct, more permeable than the boundaries defi ned by professional scopes of practice (Goodwin et al, 2005).…”
Section: Boundariesmentioning
confidence: 99%
“…On the other, we have much less formal groupings of clinical practitioners, often interprofessional, sometimes temporary confi gurations, sometimes permanent, brought together in a combined effort to deliver health care to a particular patient. We have also suggested that within the latter groupings (CoCPs) professional boundaries may be less distinct, more permeable than the boundaries defi ned by professional scopes of practice (Goodwin et al, 2005).…”
Section: Boundariesmentioning
confidence: 99%
“…The claim exemplified by the last quotation, which was more likely to be made by GPs with direct access to cardiological diagnostics, also implies that occupational barriers have in the past been sustained as much by specialists' 'supervisory control' over technology as by limitations in other occupations' knowledge or expertise (Halpern 1992, Goodwin et al 2005. Geriatricians also claimed that significant overlap existed between themselves and cardiologists in the care of heart failure patients (8/8 Again, the implication is that boundaries had relaxed, in this case as a result of the inability of cardiologists to deal with the growing numbers of heart failure patients.…”
Section: Demonstrating Competencementioning
confidence: 99%
“…Save for a few insightful studies, such as those concerned with how surgeons provide ‘tacit guidance’ when providing training in manual tasks (Prentice 2007), how practitioners manage the internal boundaries of a community of practice (Goodwin et al 2005), and how ‘professional visions’ are configured within medical environments (Mondada 2006, Koschmann et al . 2007, Hindmarsh et al forthcoming), we have little understanding of the significance of, or practice that underpins, ‘situated learning’.…”
Section: Discussion: Formal Procedures and Their Occasioned Applicationmentioning
confidence: 99%
“…Ball and Lampert 1999, Cobb et al 2001) and in quite a different way within studies of healthcare ( e.g. Timmermans and Angell 2001, Goodwin et al 2005, Prentice 2007). Once again these contributions stress the importance of interpersonal communication and social interaction as the principal vehicle in and through which people are encompassed within, and sustain, ‘communities of practice’; that is, the ways of accomplishing highly specialised activities in concert with others in ordinary everyday situations.…”
Section: Introductionmentioning
confidence: 99%